A Study on Research Problems in Data Security in Cloud Computing - Vishnupriya, M (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing has attracted considerable attention in both industry and academic. It leads to gain effectiveness deployment, efficiency development and pay on- demand in purchasing and maintaining infrastructure. The resources stored in the cloud are managed by the Cloud Service Provider. Even though, cloud computing provides more advantages to the users, there exists security problem in cloud computing. The data owner who outsources their critical data are unaware of how data being stored in the cloud and who accessing their data. This arises many security issues in cloud computing. This paper discusses several security issues that occur over the cloud and solutions offered by various researches